Selective Factors Related to Intensive Care Units’ Registered Nurses’ Competency in Caring for Terminally Ill Patients - Nupinit, Warina; Nilmanat, Kittikorn; Mutchim, Yoawarat (Journal of Thailand Nursing and Midwifery Council, 2018)
Abstract Objective: To identify selective factors and their relationship with intensive care units’ registered nurses’ competency in caring for terminally ill patients. Design: Descriptive correlational research. Methodology: Through stratifed random sampling and population ratio sampling, 250 participants were selected for this study. They were registered nurses serving in ICU wards of hospitals and medical centres in southern Thailand. Data were collected using 4 questionnaires: (1) a general information questionnaire; (2) a questionnaire on registered nurses’ perception of their competency in caring for terminally ill patients; (3) a questionnaire on registered nurses’ attitudes towards patients and dying patients; and (4) an organisation atmosphere questionnaire. All of the questionnaires were validity-checked by 3 expert scholars and validity-tested using Cronbach’s alpha coeffcient. The data were analysed using descriptive statistics, whilst the relationship that personal and environmental factors had with the registered nurses’ competency in caring for terminally ill patients in intensive care units was analysed using Pearson’s correlation coeffcient and point biserial correlation. Results: The study’s statistically signifcant fndings are as follows. First, organisation atmosphere and training on care of terminally ill patients displayed a moderately positive relationship with ICU’s registered nurses’ competency in caring for the terminally ill (r = 0.603, p < 0.01; r = 0.316, p < 0.01, respectively). Next, the nurses’ attitudes towards death, experience in caring for terminally ill patients, and education levels displayed a lowly positive relationship with their competency in caring for the terminally ill (r = 0.221, p < 0.01; r = 0.214, p < 0.01; r = 0.158, p < 0.05, respectively). On the other hand, no signifcant relationship was found between the factors of age and ICU work experience and the nurses’ competency in caring for the terminally ill. Recommendations: It is recommended that attitude-building and knowledge-enhancing training be provided for nurses to improve their competency in caring for terminally ill patients. In addition, an ICU’s working atmosphere should be made conducive to improving the competency of care of the terminally ill